Advertising, Earnings Prediction and Market Value: An Analysis of Persistent UK Advertisers. (6th August 2019) - Shah, Syed Zulfiqar Ali; Akbar, Saeed; Ahmad, Sardar; Stark, Andrew W.
Abstract: This paper examines whether major media advertising expenditures help in predicting future earnings. We consider the role of media advertising in firms' marketing efforts and posit that persistent advertisers are more likely to benefit from advertising activities in creating long‐lived intangible assets. Employing a sample of persistent UK advertisers over the period 1997–2013, we find that advertising expenditures are significantly positively associated with firms' future earnings and market value. We also report size and sector‐based differences in the association between advertising and firms' future earnings. Our additional analysis provides support for the arguments that despite the recent rise in digital advertising budgets, traditional advertising media are still effective in positively influencing firms' performance. Overall, the results of this study are consistent with the view that advertising expenditures produce intangible assets, at least for firms in certain sectors. These findings have implications for marketers in providing evidence of the value generated by firms' advertising budgets, for investors in validating the relevance of advertising information in influencing future earnings, and for accounting regulators in relation to the provision of useful insights for any future deliberations on financial reporting policies for advertising expenditures.